Bước đầu nghiên cứu cấu tạo trầm tích bở rời các sườn lồi - lõm vùng đồi núi thấp lưu vực Sông Cầu - Anh, Lại Huy; Tuấn, Tống Phúc (Vietnam Journal of Earth Sciences, 2003)
Preliminary study on structure of friable sediment of convexo-concave slope in low mountains and hills in the basin of Cau river